(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of firm size and Debt to Asset Ratio (DAR) on Return on Assets (ROA) at PT Astra International Tbk during the 2015–2024 period. The research employed a quantitative approach with an associative method. The data used were secondary data obtained from the company’s annual financial statements published by the Indonesia Stock Exchange. Data analysis techniques included classical assumption tests, multiple linear regression, correlation coefficient analysis, coefficient of determination, t-test, and F-test. The results indicate that firm size has no significant effect on ROA, with a significance value of 0.340 > 0.05. Likewise, DAR has no significant effect on ROA, with a significance value of 0.223 > 0.05. Simultaneously, firm size and DAR do not significantly affect ROA, as indicated by a significance value of 0.306 > 0.05. The coefficient of determination shows that both variables explain only 28.7% of the variation in ROA, while the remaining 71.3% is influenced by other factors outside the research model. These findings suggest that corporate profitability is not solely determined by firm size and debt levels.